2021
DOI: 10.3390/microorganisms9050913
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Sources and Genetic Control of Resistance to ToLCNDV in Cucumber

Abstract: Tomato leaf curl New Delhi virus (ToLCNDV) is a severe threat for cucurbit production worldwide. Resistance has been reported in several crops, but at present, there are no described accessions with resistance to ToLCNDV in cucumber (Cucumis sativus). C. sativus var. sativus accessions were mechanically inoculated with ToLCNDV and screened for resistance, by scoring symptom severity, tissue printing, and PCR (conventional and quantitative). Severe symptoms and high load of viral DNA were found in plants of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Recessive resistance or incomplete dominance to ToLCNDV is reported as the main inheritance model controlling the resistance in cucurbits ( Sáez et al, 2017 , 2020 , 2021 ). In this study, we investigate the process of ToLCNDV infection in a resistant and susceptible C. melo genotype, trying to correlate resistance or susceptibility with changes in transcript expression patterns and comparing them at different temporal stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recessive resistance or incomplete dominance to ToLCNDV is reported as the main inheritance model controlling the resistance in cucurbits ( Sáez et al, 2017 , 2020 , 2021 ). In this study, we investigate the process of ToLCNDV infection in a resistant and susceptible C. melo genotype, trying to correlate resistance or susceptibility with changes in transcript expression patterns and comparing them at different temporal stages.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to verify the presence or absence of ToLCNDV infection in all plants at 20 dpi, tissue-printing hybridization by digoxigenin-labeled ToLCNDV-RNA probe was performed following the procedure described in Sáez et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, screening for resistance cultivars has become the main approach in attempting to manage ToLCNDV pathogens. Until now, some studies have reported ToLCNDV resistance in the sponge gourd ( Luffa aegyptiaca ), melon ( C. melo ), pumpkin ( C. moschata ) [ 19 , 20 , 21 ], and cucumber ( Cucumis sativus ), recently [ 22 ]. However, there is a need to study and screen more resistance cultivars against ToLCNDV due to the wide broad host range of this virus as well as less advanced research in the resistance genotype.…”
Section: Introductionmentioning
confidence: 99%
“…[26] has also been reported in Bangladeshi germplasm. Bangladesh was part of India until 1947 and ToLCNDV resistant germplasm of Luffa cylindrica [27] and melon (Cucumis melo L.) [10,28,29] has also been reported in Indian accessions.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite likely that this region responsible for the ToLCNDV resistance is common among these different C. moschata accessions as the resistance to ToLCNDV in melon (Cucumis melo) is also recessive and controlled by a major locus in Chromosome 11, that maps in a region that is syntenic to that of Chromosome 8 of C. moschata [28,30]. In cucumber, monogenic recessive resistance to ToLCNDV has been recently identified, but preliminary mapping analyses show a different genomic region is implicated [29]. A single dominant gene conferring resistance to ToLCNDV also has been reported in a Japanese C. moschata accession, BSUAL-252 [31], though this is not linked to the genomic region on Chromosome 8 where the locus of the recessive gene for ToLCNDV resistance is located [31].…”
Section: Discussionmentioning
confidence: 99%